2019
DOI: 10.3390/ma13010067
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Performance of Radiata-Pine-Derived Polyvinyl Alcohol/Carbon Quantum Dots Fluorescent Films

Abstract: In this study, the low-cost processing residue of Radiata pine (Pinus radiata D. Don) was used as the lone carbon source for synthesis of CQDs (Carbon quantum dots) with a QY (The quantum yield of the CQDs) of 1.60%. The CQDs were obtained by the hydrothermal method, and +a PVA-based biofilm was prepared by the fluidized drying method. The effects of CQDs and CNF (cellulose nanofibers) content on the morphology, optical, mechanical, water-resistance, and wettability properties of the PVA/CQDs and PVA/CNF/CQDs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 82 publications
2
25
0
Order By: Relevance
“…The quantum dots prepared using hydrochloric acid appear to be the of a polydispersive nature and have the highest range of size, which is from 2 nm to 11 nm. It has been reported that the CQDs' size affects its luminescence behavior [1][2][3]. Thus, it can be assumed that the right choice of the carbonizing agent enables the preparation of nanodots with desired properties using the hydrothermal method, which is known to be challenging.…”
Section: Scheme 1 Carbon Quantum Dots With the Free Carboxylic Groupmentioning
confidence: 99%
See 4 more Smart Citations
“…The quantum dots prepared using hydrochloric acid appear to be the of a polydispersive nature and have the highest range of size, which is from 2 nm to 11 nm. It has been reported that the CQDs' size affects its luminescence behavior [1][2][3]. Thus, it can be assumed that the right choice of the carbonizing agent enables the preparation of nanodots with desired properties using the hydrothermal method, which is known to be challenging.…”
Section: Scheme 1 Carbon Quantum Dots With the Free Carboxylic Groupmentioning
confidence: 99%
“…Fluorescence spectra of the raw carbon dots (a: Dot-1; d: Dot-2; g: Dot-3; j: Dot-4) are typical for these quantum nanomaterials [2,4,6,8,37,38,43,44]. There is an obvious emission dependence on the visible excitation wavelength, which is typical for quantum nanobojects below 10 nm in size due to the surface defects, conjugated π-domains, as well as crystalline structure disturbance [1][2][3]. One may observe that the choice of the carbonizing agent has a significant impact on the PL properties, which proves different PL intensity of the unmodified CQDs.…”
Section: Spectroscopic Properties Studymentioning
confidence: 99%
See 3 more Smart Citations